Muscle injury after low-intensity downhill running reduces running economy - Baumann, C. W.; Green, M. S.; Doyle, J. A.; Rupp, J. C.; Ingalls, C. P.; Corona, B. T. (The Journal of Strength and Conditioning Research, 2014)
Contraction-induced muscle injury may reduce running economy (RE) by altering motor unit recruitment, lowering contraction economy, and disturbing running mechanics, any of which may have a deleterious effect on endurance performance. The purpose of this study was to determine if RE is reduced 2 days after performing injurious, low-intensity exercise in 11 healthy active men (27.5 ± 5.7 years; 50.05 ± 1.67 VO2peak). Running economy was determined at treadmill speeds eliciting 65 and 75% of the individual's peak rate of oxygen uptake (VO2peak) 1 day before and 2 days after injury induction. Lower extremity muscle injury was induced with a 30-minute downhill treadmill run (6 × 5 minutes runs, 2 minutes rest, -12% grade, and 12.9 km/h that elicited 55% VO2peak. Maximal quadriceps isometric torque was reduced immediately and 2 days after the downhill run by 18 and 10%, and a moderate degree of muscle soreness was present. Two days after the injury, steady-state VO2 and metabolic work (VO2 L/km) were significantly greater (4-6%) during the 65% VO2peak run. Additionally, postinjury VCO2, VE and rating of perceived exertion were greater at 65% but not at 75% VO2peak, whereas whole blood-lactate concentrations did not change pre-injury to postinjury at either intensity. In conclusion, low-intensity downhill running reduces RE at 65% but not 75% VO2peak. The results of this study and other studies indicate the magnitude to which RE is altered after downhill running is dependent on the severity of the injury and intensity of the RE test.